Cross-Reactivity, Epitope Mapping, and Potency of Monoclonal Antibodies to Class 5 Fimbrial Tip Adhesins of Enterotoxigenic Escherichia coli - Liu, Yang (Infect Immun, 2020)
Enterotoxigenic Escherichia coli (ETEC) is a leading diarrheagenic bacterial pathogen among travelers and children in resource-limited regions. Adherence to host intestinal cells mediated by ETEC fimbriae is believed to be a critical first step in ETEC pathogenesis. These fimbriae are categorized into related classes based on sequence similarity, with members of the class 5 fimbrial family being the best characterized. The eight related members of the ETEC class 5 fimbrial family are subdivided into three subclasses (5a, 5b, and 5c) that share similar structural arrangements, including a fimbrial tip adhesin. However, sequence variability among the class 5 adhesins may hinder the generation of cross-protective antibodies. To better understand functional epitopes of the class 5 adhesins and their ability to induce intraclass antibody responses, we produced 28 antiadhesin monoclonal antibodies (MAbs) to representative adhesins CfaE, CsbD, and CotD, respectively. We determined the MAb cross-reactivities, localized the epitopes, and measured functional activities as potency in inhibition of hemagglutination induced by class 5 fimbria-bearing ETEC. The MAbs’ reactivities to a panel of class 5 adhesins in enzyme-linked immunosorbent assays (ELISAs) revealed several reactivity patterns, including individual adhesin specificity, intrasubclass specificity, intersubclass specificity, and class-wide cross-reactivity, suggesting that some conserved epitopes, including two conserved arginines, are shared by the class 5 adhesins. However, the cross-reactive MAbs had functional activities limited to strains expressing colonization factor antigen I (CFA/I), coli surface antigen 17 (CS17), or CS1, suggesting that the breadth of functional activities of the MAbs was more restricted than the repertoire of cross-reactivities measured by ELISA. The results imply that multivalent adhesin-based ETEC vaccines or prophylactics need more than one active component to reach broad protection.